Diagnostic yield of stool culture and probable predictive factors: A single-center experience - Alzaher, Mohamad Zaki; Almugahwi, Abdulelah Abdulrahman; Almulla, Ali Abdullah; Almeer, Hashim Hadi; Alshammasi, Mustafa Mohammed; El-Badry, Ayman A. (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Stool analysis is commonly performed to diagnose certain gastrointestinal diseases. The diagnostic yield of stool culture,  a method of stool analysis, is variable worldwide and is unclear in the Kingdom of Saudi Arabia. This study was conducted to determine the diagnostic yield of stool culture from the year 2008 to 2020 and to determine the predictors for a positive stool culture. Furthermore, antibiotic susceptibility patterns of the detected copro-pathogens in the same time period were collected and studied.Methods: This is a retrospective case-control study in which patients’ data was collected from the hospital’s electronic health record. The results of all stool analyses performed from 2008 to 2020 and associated patients’ characteristics were collected.  Characteristics of cases with a positive stool culture were compared to the characteristics of those without to identify the predictors for positive stool cultures.Results: Copro-pathogens were detected in 89.4% of cultured stool samples. Salmonella spp (1590/1775, 89.6%) was the most common organism followed by Shigella spp. (84/1775, 4.7%) and Campylobacter spp (45/1775, 2.5%). Male sex, the 1-5 age group, positive fecal occult blood test results, and positive stool leukocyte test results were associated with a positive stool culture result. Cultured copro-pathogens were highly sensitive to Trimethoprim/Sulfamethoxazole and Ampicillin.Conclusions: Stool analysis was found to be a test of high diagnostic yield. However, there is still a need for more studies on this subject with a focus on possible predictive factors for specific organisms.